Bromocriptine treatment of female infertility: report of 13 pregnancies. Issue 5998 (20th December 1975) - Thorner, M O; Besser, G M; Jones, A; Dacie, J; Jones, A E
Abstract : Thirteen pregnancies occurred in 12 women who were treated with bromocriptine for infertility. Pretreatment prolactin levels were recorded in 11 patients and were normal in three. Five patients had suspected pituitary tumours, and they received irradiation to prevent swelling of the pituitary and the consequent visual field defects caused by the pressure of the swollen gland on the optic nerve. Ten of the 13 pregnancies have come to term, and all the babies were normal. When a patient with a pituitary tumour developed a visual field defect in the 38th week of pregnancy labour was induced and the defect disappeared after delivery. No multiple pregnancies occurred and there were no major complications.